From Preferences to Ingredients - Customised Beverage Product Formulation Workshop - Makatsoris, Harris; McMulloch, Josie; Wagner, Christian (Cranfield University, 2018)
This work aims to test if we can create tailored orange drinks from a consumer's description of their ideal drink. Their description is converted into ingredient quantities, with which a drink is created using our beverage formulator. The consumer then tastes the drink and assesses if it correctly matches what they requested.
Keywords: 'Product Formulation'; 'Interval valued sensory evaluation'; 'continuous manufacturing'; 'Food Processing'; 'Food Engineering'; 'Manufacturing Management'; 'Manufacturing Processes and Technologies (excl. Textiles)'; 'Process Control and Simulation'